Mapping the capacitance of self-assembled monolayers at metal/electrolyte interfaces at the nanoscale by in-liquid scanning dielectric microscopy. Issue 40 (12th October 2020) - Millan-Solsona, Ruben; Checa, Martí; Fumagalli, Laura; Gomila, Gabriel
Abstract : The specific capacitance of ultrathin organic self-assembled monolayers at metal/electrolyte interfaces is measured with nanoscale spatial resolution. Abstract : Organic self-assembled monolayers (SAMs) at metal/electrolyte interfaces have been thoroughly investigated both from fundamental and applied points of view. A relevant figure of merit of metal/SAM/electrolyte interfaces is the specific capacitance, which determines the charge that can be accumulated at the metal electrode. Here, we show that the specific capacitance of non-uniform alkanethiol SAMs at gold/electrolyte interfaces can be quantitatively measured and mapped at the nanoscale by in-liquid scanning dielectric microscopy in force detection mode. We show that sub-100 nm spatial resolution in ultrathin (<1 nm) SAMs can be achieved, largely improving the performance of current sensing characterization techniques. The present results provide access to study the dielectric properties of metal/SAM/electrolyte interfaces at scales that have remained unexplored until now.